IMPLEMENTASI VISI SUSTAINABLE DEVELOPMENT GOALS(SDGs) PADA PROGRAM BERBASIS MASYARAKAT DI ERA PANDEMI - Bahrul Jalaali (Institut Teknologi Dirgantara Adisutjipto, 2021)
The COVID-19 pandemic situation is directly affecting both the health and economic sectors, especially in Indonesia. The synergy between university, community, and practitioner is needed as an effort for COVID-19 prevention and to help driving the economical sector in terms of the community service program. Sustainable development goals (SDGs) are the global actions that will be referred to as the community service program. The indicator analysis between global action and the outcomes of the community service program is performed to give further the recommendation related to the globally oriented program on solving a local problem. As a scheme of university tri dharma, SGDs based community service program has been implemented to the COVID-19 affected region, namely, a small business of convection in Wedi, Klaten, and health equipment distribution towards Wonosari hospital (RSUD). Program is evaluated in terms of ethical, social and economical dimension, yet the result intepretation is presented as well. The results of these activities have achieved the collaboration of community service activities with the mission of the SDGs on the implementation of the economy, health, and partnership sectors.